2008
DOI: 10.1038/ijo.2008.220
|View full text |Cite
|
Sign up to set email alerts
|

Early overweight and pubertal maturation—pathways of association with young adults’ overweight: a longitudinal study

Abstract: Objective: Objectives of this study were to examine the prospective association of childhood body mass index (BMI) and overweight and pubertal stages with BMI and overweight in early adulthood independent of each other. Design: A population-based prospective birth cohort. Subjects: We used a population-based prospective birth cohort of 2897 (52% men) young adults who were born during 1981-1983 in Brisbane, Australia, and for whom we had puberty stages using Tanner scale at 14 years and measured BMI at 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 40 publications
(67 reference statements)
3
52
3
2
Order By: Relevance
“…We replicated previous findings that earlier pubertal timing is associated with higher adult BMI (Kindblom et al 2006;Mamun et al 2009;Widen et al 2012) (Fig. 1b).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We replicated previous findings that earlier pubertal timing is associated with higher adult BMI (Kindblom et al 2006;Mamun et al 2009;Widen et al 2012) (Fig. 1b).…”
Section: Discussionsupporting
confidence: 91%
“…Because research has shown that men's muscularity, strength, and facial and vocal characteristics are especially likely to have been targets of sexual selection (Hill et al 2013;Lassek and Gaulin 2009;Doll et al 2014), we focused on these traits. We also attempted to replicate previous associations with mental rotation ability (Beltz and Berenbaum 2013) and BMI (Mamun et al 2009;Widen et al 2012).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to Oken et al's study, off spring of mothers with excessive weight gain during pregnancy, as defi ned by the IOM, were more likely to be overweight (OR=1.3, 95% CI: 1.0 to 1.8) and obese (OR=1.5, 95% CI: 1.0 to 2.1) at 21 years of age compared with those with inadequate weight gain. Although there was a posi ve associa on with adequate GWG and risk of overweight or obesity at age 21 years, results were insignifi cant 11 .…”
Section: Maternal Gestational Weight Gain and Childhood Adipositymentioning
confidence: 89%
“…As excessive gesta onal weight gain (GWG) has been correlated with childhood and later in life overweight and obesity, the importance of appropriate GWG has gained increasing a en on in recent mes [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Mo vated by recent research on the changing characteris cs of the child-bearing popula on, the Ins tute of Medicine (IOM) revised GWG guidelines in 2009 to include a specifi c recommenda on for obese women, This work is licensed under a Creative Commons Attribution 3.0 License.…”
Section: Introductionmentioning
confidence: 99%